Stalin - Kuromiya, Hiroaki (Harlow, England ; New York : Pearson/Longman, 2005)
"Hiroaki Kuromiya argues that the key to understanding Stalin lies in the fact that he lived solely for the purpose of shaping the body politic through the pursuit and exercise of power. Whatever private emotions Stalin had - whether affection, lust, hatred, or vindictiveness - he channelled to political ends and subsumed in his quest for power. Even ordering the deaths of people close to him evoked no special emotion because he deemed it necessary for the higher order. Kuromiya lucidly and systematically explains Stalin's use of terror as a political action - how Stalin viewed political terror, why he used terror so extensively, and how he felt about the deaths of millions." "Drawing on the author's extensive research into recently uncovered documents on Stalin's life, and reflecting the current state of knowledge in the field, this concise biography untangles the enigma of Stalin and elucidates his political thought and action. The world order changed irreversibly with the establishment of the Soviet Union. Kuromiya argues that without understanding Stalin, one cannot understand the twentieth century."--Jacket
From Georgia to Russia -- Revolution and civil war -- Struggle for power -- 'Revolution from above' -- Famine and terror -- War -- Struggle for survival -- Twilight of the god.
Includes bibliographical references (pages 212-216) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Stalin, Joseph, -- 1878-1953.; Stalin, Joseph, -- 1878-1953; Sowjetunion -- Sovet ministrov; Stalin, Iosif V; Heads of state -- Soviet Union -- Biography; Soviet Union -- History -- 1925-1953.; Chefs d'État -- URSS -- Biographies; URSS -- Histoire -- 1925-1953.; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Heads of state; Soviet Union; Machtpolitik; Staatshoofden; 1925-1953; Biography; History; Biographies; Biographies; Biographies